2013
DOI: 10.1007/s00268-013-2288-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Clinically Significant Delayed Gastric Emptying After Subtotal Stomach‐Preserving Pancreatoduodenectomy

Abstract: DGE after SSPPD is strongly linked to the occurrence of other postoperative intra-abdominal complications such as pancreatic fistula. The incidence rate of primary DGE after SSPPD was 4 %. Although the ISGPS classification of DGE is clearly applicable, the grades do not explain why DGE occurs. Primary and secondary DGE should therefore be defined separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 58 publications
4
25
0
Order By: Relevance
“…This correlation is consistent with those found in other published series[27,28]. In a large multi-institutional study of the American College of Surgeons National Surgical Quality Improvement Program Pancreatectomy Demonstration Project, only pancreatic fistula, postoperative sepsis, and reoperation were independently associated with DGE in 711 patients undergoing PD or total pancreatectomy[27].…”
Section: Discussionsupporting
confidence: 89%
“…This correlation is consistent with those found in other published series[27,28]. In a large multi-institutional study of the American College of Surgeons National Surgical Quality Improvement Program Pancreatectomy Demonstration Project, only pancreatic fistula, postoperative sepsis, and reoperation were independently associated with DGE in 711 patients undergoing PD or total pancreatectomy[27].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the incidence of DGE, especially grade B or C was significantly higher in the SSPPD group than in the ACPD group. The rate of DGE grade B or C in the SSPPD group was 16%, which was similar to the reported results of the SSPPD in the recent retrospective analyses [29]. Furthermore, SSPPD rather than ACPD was an independent risk factor for grade B or C DGE, and the postoperative nutritional status was comparable between the ACPD group and the SSPPD group.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, DGE was identified as a risk factor contributing to delayed PPH. Several reports have demonstrated that a higher DGE morbidity often signified a higher incidence of PF or intra‐abdominal abscess . As such, a small pancreatic duct or postoperative DGE contributed to a higher incidence of PF or intra‐abdominal infection, which might further increase the risk of PPH.…”
Section: Discussionmentioning
confidence: 99%